2023
DOI: 10.3390/medicina59020374
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Patient Position in the Surgical Treatment of Supracondylar Fractures of the Humerus: Comparison of Prone and Supine Position

Abstract: Background and Objectives: Supracondylar fractures of the humerus (SCHF) make up about one-third of pediatric fractures and are the most common elbow fractures in children. Reduction and fixation of SC fractures can be performed with the patient in the prone or supine position. However, the role of the patient’s position during surgery is still unclear. The purpose of this systematic review is to evaluate, based on data from the literature, the role of patient position during closed reduction and fixation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In this study, all children who received surgery were operated on in the supine position. In the literature, no differences have been described in terms of functional and radiological outcomes between prone and supine positioning, and positioning is dependent on the habits and experience of the surgeons and anesthesiologists [ 40 ]. In addition, this study showed that although the majority of patients were clinically fully functional at the end of their treatment, functional and neurological deficits scarcely occurred in type I fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all children who received surgery were operated on in the supine position. In the literature, no differences have been described in terms of functional and radiological outcomes between prone and supine positioning, and positioning is dependent on the habits and experience of the surgeons and anesthesiologists [ 40 ]. In addition, this study showed that although the majority of patients were clinically fully functional at the end of their treatment, functional and neurological deficits scarcely occurred in type I fractures.…”
Section: Discussionmentioning
confidence: 99%
“…While the supine position is most often used for supracondylar humeral fracture reduction, both supine and prone positioning of the patient has been used. A recent systematic review showed comparable results for closed reduction and pinning in both positions [19]. However, as sideward displaced fractures may require switching to open reduction, we do not recommend using prone positioning for this fracture subtype.…”
Section: Discussionmentioning
confidence: 81%
“…The latter arises from kinking or tangling of soft tissues against the pin in the process of pin insertion [20]. The well-known techniques to reduce the risk of iatrogenic ulnar nerve injury, including the miniopen approach over the medial epicondyle [10], intraoperative prone positioning [22,23], and Mubarak and Davids' maneuver [14,15], are designed to prevent direct penetration of the ulnar nerve. The rationale behind the Mubarak and Davids' maneuver is based on the tendency of the ulnar nerve to migrate over the anterior to the medial epicondyle when the elbow is hyperflexed >90° [19][20][21]24].…”
Section: Discussionmentioning
confidence: 99%